Boredom as the originator of a desideratum - reflections on the creative and suppressive consequences of boredom in the school context - Zeißig, Anke (Frontiers in Sociology, 2023)
Children who are bored begin to draw, do crafts, fidget - or do something bad. Others fall silent, withdraw, or dull. Research on school-related boredom has focused primarily on its negative consequences, such as decreased cognitive performance, loss of motivation, or attention, or disruptive behavior. This repressive aspect of boredom is also contrasted by the notion that boredom can promote creative performance. This paper attempts to focus on creative and repressive consequences of boredom in the interplay of personality traits with behavioral possibilities in school situations, and between situational experiences and constituent developmental processes. It is proposed that boredom is a gauge of the learner's resonance with school content, learning, or developmental relationships and that both creative and repressive potentials are inherent in boredom.